ANALISIS LOG SISTEM PADA SECURITY INFORMATION AND EVENT MANAGEMENT UNTUK MENDETEKSI SERANGAN DDOS - Gede Angga Widya Putra (2023)
One area of technology that is growing rapidly today is information and communication technology. The form of advances in information and communication technology that we often encounter in everyday life is the Internet (Interconnected Network). Through the internet, various individuals and organizations can exchange information with each other. However, this increase is also directly proportional to the emergence of various kinds of security holes that are often exploited by electronic criminals to gain financial gain. This can be seen from the number of cases of DDoS attacks on organizations. Distributed Denial of Service attacks are carried out by flooding a server or host, causing the victim host to run out of resources to serve other users. To overcome this, the author uses Security Information and Event Management (SIEM). SIEM is a method for monitoring, analyzing, giving warnings and automating responses to incidents. This research is expected to be able to explain the results of testing, analysis, and solutions regarding the problem of DDoS attacks on SIEM.